Three Generations of Intergenerational Transmission of Neighbourhood Context - Lina Hedman; Maarten van Ham; Tiit Tammaru (Institute of Labor Economics (IZA), 2017)
The literature on intergenerational contextual mobility has shown that neighbourhood status is partly "inherited" from parents to children where children who spend their childhood in deprived neighbourhoods are more likely to live in such neighbourhoods also as adults. It has been suggested that such transmission of neighbourhood status also is relevant from multiple generation approach. To our knowledge, however, this has only been confirmed by simulations and not empirical research. This study uses actual empirical data covering 25 years and the full Swedish population to investigate intergenerational similarities in neighbourhood status of three generations of Swedish women. Findings suggest that the neighbourhood environments of Swedish women are correlated with the neighbourhood statuses of their mothers and, to some extent, grandmothers. We also find an effect of distance where intergenerational transmission is stronger for those remaining close. Whereas women whose mothers and grandmothers live in high-income areas benefit from staying close, women whose mothers and grandmothers live in low-income areas do better if they live further away. These results are robust over two different analytical strategies – comparing neighbourhood status of the three generations at similar ages and at the same point in time – and two different spatial scales. We argue that the finding of such effects in (relatively egalitarian) Sweden implies that similar, and possibly stronger, patterns are likely to exist in other countries as well.
Keywords: I30; J60; R23; 330; intergenerational transmission; neighbourhood; low-income neighbours; register data; Sweden